Analisis Status Hadith Syafaat Huffaz Al-Quran Kepada 10 Ahli Keluarga: Analysis on the Status of the Hadith Intercession of Huffaz Al-Quran to 10 Family Members - Ahmad, Khadher`; Md. Ariffin, Mohd Farhan (Online Journal of Research in Islamic Studies, 2019)
In Malaysia, among the famous weak hadiths is the intercession of hafiz al-Quran to 10 members of his family. As a result, the hadith has established trust and continues to be thicker within the society. Even in a virtual site such as facebook, twitter, blogs and so on, many of these hadiths are addressed when it comes to the importance of hafiz al-Quran. Most notably, the promotion of admission to the Quranic centers in Malaysia is still using the argument for years. Therefore, the effort to explain to the public is important to cultivate the authentic hadiths in religious life. As one of the means, this article attempts to analyze the hadith through the study of the narrator network, the support of the narration path (mutaba'at and syawahid) existing based on the study of tarajim al-Ruwat and Jarh wa al-Ta'dil based on ulum al- Hadith. The result is that hadith is not valid (munkar: very weak) and in it there is the narrator of matruk, lying a part and majhul (unknown) by the scholars of 'hadith. It is hoped that this study will be useful for all Muslims.